2020
DOI: 10.1016/j.celrep.2020.108124
|View full text |Cite
|
Sign up to set email alerts
|

OPG Production Matters Where It Happened

Abstract: Osteoprotegerin (OPG) is a circulating decoy receptor for RANKL, a multifunctional cytokine essential for the differentiation of tissue-specific cells in bone and immune systems such as osteoclasts, medullary thymic epithelial cells (mTECs), and intestinal microfold cells (M cells). However, it is unknown whether OPG functions only at the production site or circulates to other tissues acting in an endocrine fashion. Here we explore the cellular source of OPG by generating OPG-floxed mice and show that locally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…It is nicely demonstrated by Akiyama et al that Spib remarkably limits the development and maturation of mTECs but promotes CD80 expression in mature mTECs (Akiyama et al, 2014). Importantly, RANKL stimulation consecutively induces Spib expression in TECs and Spib facilitates expression of OPG protein, which competitively inhibits RANKL-RANK interactions as a decoy receptor of RANKL, in mTECs by maintenance of the hypomethylated states in Opg (Akiyama et al, 2014;Tsukasaki et al, 2020). Thus, SPIB-mediated negative feedback regulation of RANKL signaling limits mTEC development in neonates but not in embryos by forming RANKL-NF-κB-SPIB-OPG regulating loop in mTECs (Akiyama et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…It is nicely demonstrated by Akiyama et al that Spib remarkably limits the development and maturation of mTECs but promotes CD80 expression in mature mTECs (Akiyama et al, 2014). Importantly, RANKL stimulation consecutively induces Spib expression in TECs and Spib facilitates expression of OPG protein, which competitively inhibits RANKL-RANK interactions as a decoy receptor of RANKL, in mTECs by maintenance of the hypomethylated states in Opg (Akiyama et al, 2014;Tsukasaki et al, 2020). Thus, SPIB-mediated negative feedback regulation of RANKL signaling limits mTEC development in neonates but not in embryos by forming RANKL-NF-κB-SPIB-OPG regulating loop in mTECs (Akiyama et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In OPG-floxed mice, it showed that locally produced OPG is important for bone and immune homeostasis rather than circulating OPG. It suggests that OPG limits its role within the tissue where it was produced [ 51 ].…”
Section: Molecular Biology Of Osteoporosismentioning
confidence: 99%
“…International Publisher osteoblast lineage cells [13,14]. Persistent elevation of PTH (as in calcium deficiency) causes skeletal catabolic effects by elevating RANKL expression and lowering OPG expression of osteoblasts [15,16].…”
Section: Ivyspringmentioning
confidence: 99%
“…Osteoprotegerin (OPG) acts as a decoy receptor of RANKL by preventing the binding between RANK and RANKL. Both cytokines are secreted by osteoblast lineage cells 13 , 14 . Persistent elevation of PTH (as in calcium deficiency) causes skeletal catabolic effects by elevating RANKL expression and lowering OPG expression of osteoblasts 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%